Innovation and firm’s performance among Malaysian manufacturing SME’s - Abdullah Al- Mamun; Rajennd Muniady; Syed Ali Fazal (Penerbit Universiti Malaysia Kelantan, 2019)
SMEs commonly compete based on price and quality; however, these may not be enough to gain competitive advantages, sustainability, and superior performance in today’s competitive global business environment. As this book is interested in explaining the nature of innovation of manufacturing SMEs, their capacity to attain the perceived attributes of innovation (i.e., measure the economic profi tability, initial cost, decrease in discomfort, savings in time and eff ort, immediacy of reward, social benefi ts, and hazards removed, together with the alignment of existing setup, norms and values, abilities to deal with complex innovation, capacity to adopt innovation on a trial basis and the ability to observe the outcome of similar innovation adoption) is explored on, as they are important instruments for innovation adoption and the performance of manufacturing SMEs in Malaysia. It is also crucial that SMEs align their strategies through acquiring, disseminating, and responding to market information, building customer intelligence by examining customers’ needs and preference, and exploiting new opportunities, which is a part of the fi ndings in this book. It also highlights the positive role of prior condition, knowledge, and risk orientation, which implies that it is crucial for Malaysian manufacturing SMEs to accept new changes or new innovation, gather innovation related knowledge and build their risk-taking capabilities to accommodate innovation adoption. Besides confi rming the conceptual model and contributing to the theories, this book also off ers implications and tools for manufacturing SMEs and policy makers focused on providing a supportive system for innovationled SMEs for a sustainable economic development.